Studi Sistematik Jenis-Jenis Parenting Pada Anak Serta Implikasinya Terhadap Akhlak - Abu Warasy Batula; Ahmad Syakir Wildani; Nabilah Safira Salamat; Nadhilah Nur Sabrina; Siti Hamidah (Institut Nalanda, 2023)
Different types of parenting styles will certainly have a different impact on children's morals. This study examines 3 types of parenting which aims to determine the impact of these types of parenting on children's morals. The method used is a qualitative approach design by applying systematic studies, which results that Authority Parenting tends to restrain and limit children, so that children feel constrained and insecure, then Authoritative Parenting gives more freedom to children, but remains under the supervision of parents, so that children more open, independent, and able to discuss with parents. Unlike the previous parenting style, Permissive Parenting is a parenting style that provides complete freedom, without parental intervention, which causes children to lose their way. Reviewing the three types of parenting, Authoritative Parenting is the best type of parenting to be implemented by parents to children, because it has the best implications for children's morals.